1996
DOI: 10.2165/00007256-199621030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Development of Public Policy and Physical Activity Initiatives Internationally

Abstract: Epidemiological, pathological, clinical, and experimental studies over the past 40 years convincingly show that physical inactivity and low physical fitness contribute substantially to the major chronic diseases prevalent in industrialised societies. Several industrialised countries around the world report increases in physical activity participation among adults in recent years, but the prevalence of inactivity remains high. These increases in voluntary exercise are at least partially offset by decreasing dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…The greatest difference in mortality due to cardiovascular disease and some types of cancer recorded between categories of sedentary (little or no physically active persons) and the first following categories of physically active, or when sedentary people become moderately physically active 39 . To improve overall health status it is enough to reach and maintain the average level of aerobic capacity 32 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The greatest difference in mortality due to cardiovascular disease and some types of cancer recorded between categories of sedentary (little or no physically active persons) and the first following categories of physically active, or when sedentary people become moderately physically active 39 . To improve overall health status it is enough to reach and maintain the average level of aerobic capacity 32 .…”
Section: Discussionmentioning
confidence: 98%
“…Epidemiological studies in the second half of the 20th century confirmed a dose dependent link between physical activity and physical fitness [37][38][39][40] . The greatest difference in mortality due to cardiovascular disease and some types of cancer recorded between categories of sedentary (little or no physically active persons) and the first following categories of physically active, or when sedentary people become moderately physically active 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the contents of health promotion activities could vary according to the differences related to age, gender and other socioeconomic and cultural variables of the targeted populations 51,56 . In any case, prescribing exercise for health by physicians and other health professionals may be beneficial in primary care 57,58 , while scientists and public health officials need to turn attention to public policy and legislative initiatives to restructure social environments to encourage more physical activity and discourage sedentary and other unhealthy habits 2,7,[59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…Muitos estudos têm revelado que a realização de atividade física diária é essencial para a melhora da saúde e da qualidade de vida do indivíduo, pois o sedentarismo está associado ao aparecimento de algumas enfermidades, principalmente as doenças cardiovasculares (BLAIR et al, 1996;MATSUDO et al, 2002). Nessa perspectiva, a melhoria da aptidão cardiorrespiratória, o aumento da massa muscular magra, a promoção da saúde, o bemestar e as questões estéticas têm sido os fatores apontados como os responsáveis por levar as pessoas a aderirem a um programa de exercício físico (MATSUDO et al, 2002).…”
Section: Introductionunclassified